Germination performance of tobacco varieties in response to different water potentials, priming and post - priming storage durations - Ncube, B; Rukuni, D; Madanzi, T; Mahohoma, W; Manjeru, P; Handiseni, M (Academic Journals, 2020)
Sub optimal seed germination and seedling establishment are major problems in tbacco (Nicotiana tabacum L) transplant production maybe due to dormancy, low soil moisture and poor seed to media contact in the float tray system . Seed priming in which seeds imbibe water or osmotic solutions followed by drying offers rapid germination and uniform seedling establishment.